1998
DOI: 10.1007/978-94-015-9008-2_5
|View full text |Cite
|
Sign up to set email alerts
|

Agroforestry in the management of sloping lands in Asia and the Pacific

Abstract: Abstract. Steeply sloping lands are widespread in the tropics. An estimated 500 million people practice subsistence agriculture in these marginal areas. Continued population growth has led to the intensified cultivation of large areas of the sloping lands, exacerbating the problem of soil erosion. Although research shows that alley cropping and other contour agroforestry systems can stabilize the sloping lands, these systems have not been widely adopted by farmers.The Framework for Evaluating Sustainable Land … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 7 publications
0
29
0
1
Order By: Relevance
“…The MAPE values obtained are shown in Table 6. 2 5.663% DMU 7 2.069% DMU 3 2.256% DMU 8 1.124% DMU 4 4.001% DMU 9 14.513% DMU 5 5.021% DMU 10 7.046%…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MAPE values obtained are shown in Table 6. 2 5.663% DMU 7 2.069% DMU 3 2.256% DMU 8 1.124% DMU 4 4.001% DMU 9 14.513% DMU 5 5.021% DMU 10 7.046%…”
Section: Resultsmentioning
confidence: 99%
“…DMU5 always keeps a lower "technological changes" score, indicating that it has not actively improved its technology. Thus, DMU5 requires further investigation into the causes that lead to its tardiness on technology 5 , other DMUs had experienced an upward technological change, though most of them had experienced an efficiency drop during 2013-2014. This implies most of these DMUs had continued to improve their technological capabilities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil conservation effects of hedgerow systems are discussed further in this volume by Craswell (1997). The various mechanisms of tree-soil-crop interactions in HI with respect to soil fertility, competition and weed control are reviewed in the subsequent sections.…”
Section: Processmentioning
confidence: 99%
“…However, this is not the case in large areas of the tropics (Meijer et al 2015;Jepma 2013;Dahlquist et al 2007;Kiptot et al 2007;Craswell et al 1998). The research reported in this paper addresses this issue by analyzing the value of existing agroforestry systems, investigating their economic and social potential relative to swidden farming.…”
mentioning
confidence: 99%